FIDUSIA TERHADAP HAK MILIK KENDARAAN BERMOTOR DALAM PERJANJIAN PEMBIAYAAN - Girang Jayanto (Universitas Muhammadiyah Metro, 2019)
Today, many consumer finance companies, especially motorcycle financing, are experiencing rapid development and have sprung up with offers of various convenience. Finance company engaged in the financing of motorcycles, specifically for the brands of Honda, Yamaha and Suzuki through consumer financing agreements with the guaranteed surrender of ownership rights in a fiduciary manner. Based on the results of research and discussion obtained that the status of ownership of motor vehicles in the consumer agreement is on the debtor. However, because the motorized vehicle is used as a fiduciary guarantee, the ownership rights of the motor vehicle are transferred to the consumer finance company until the payment of all debtor loan installments is paid. The legal consequence of this fiduciary transfer of ownership rights is that the debtor no longer holds the ownership rights to the motorcycle and only has the borrower's right to use the motorcycle. Transfer of ownership from the debtor to the creditor results in the debtor not having the right to hand over the motorbike to another party as it is being transferred because the motorcycle is collateral for the debtor's debt to Perusahaan Pembiayaan.